Yahoo Answers: Answers and Comments for Math help! *10 points!* Polynomials and Zeros? [Mathematics]
Copyright © Yahoo! Inc. All rights reserved.
https://answers.yahoo.com/question/index?qid=20110222135231AA99otu
From Small Town Dreamer
enUS
Tue, 22 Feb 2011 13:52:31 +0000
3
Yahoo Answers: Answers and Comments for Math help! *10 points!* Polynomials and Zeros? [Mathematics]
292
38
https://answers.yahoo.com/question/index?qid=20110222135231AA99otu
https://s.yimg.com/zz/combo?images/emaillogous.png

From Anonymous: Since you have the zeros already you can easil...
https://answers.yahoo.com/question/index?qid=20110222135231AA99otu
https://answers.yahoo.com/question/index?qid=20110222135231AA99otu
Tue, 22 Feb 2011 14:02:36 +0000
Since you have the zeros already you can easily find the function by going backwards from the zeros.
say:
X=4 subtract 4
X4=0
X=3 subtract 3
X+3=0
X=3 subtract 3
X3=0
X=0 subtract 0
X0=0 => X=0
now multiply those 4 equations to get the function.
f(X)=X(X4)(X+3)(X3)
that would be the function with those zeros.
same thing with this problem
X=5
X+5=0
X=0
X=1
X1=0
again multiply the zeros out
f(x)=X(X+5)(X1)
expanding the function we get
f(x)=X^3 + 4X^2  5X
hope that helps

From offer: For this actual issue 0's of the Polynomia...
https://answers.yahoo.com/question/index?qid=20110222135231AA99otu
https://answers.yahoo.com/question/index?qid=20110222135231AA99otu
Tue, 04 Oct 2016 03:14:08 +0000
For this actual issue 0's of the Polynomial ability the answer of 2x^2  8x + 6 = 0, or 2(xa million)(x3)=0, or the fee of x for which fee of the expression will become 0. for that reason if 2(xa million)(x3)=0 then it ability made from 2 , (xa million) & (x3) 0. considering 2 cant be equl to 0, so the two the fee of xa million or that of x3 = 0. which means that the two x=a million or 3. Thats it.

From Davis P: (x4)(x+3)(x3)(x0)
x^4 4 x^3 9 x^2 +36 x
...
https://answers.yahoo.com/question/index?qid=20110222135231AA99otu
https://answers.yahoo.com/question/index?qid=20110222135231AA99otu
Tue, 22 Feb 2011 14:00:51 +0000
(x4)(x+3)(x3)(x0)
x^4 4 x^3 9 x^2 +36 x
(x+5)(x)(x1) = x^3 +4 x^2  5 x